2015
DOI: 10.1007/s11547-015-0562-9
|View full text |Cite
|
Sign up to set email alerts
|

Anal cancer FDG-PET standard uptake value: correlation with tumor characteristics, treatment response and survival

Abstract: Our data suggest that pre-treatment FDG-PET/CT SUVmax cannot directly predict tumor response and survival, but it is strongly associated with tumor characteristics such as primary tumor stage and histology, being the first one of the most important and validated prognostic factors for anal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…This is in line with the results of a prospectively conducted study of Deantonio et al including 55 patients. They observed a statistically significant correlation between SUV max and T-stage of patients and no association with treatment response or survival of patients [12]. Similarly, baseline PET uptake parameters such as SUV max and SUV mean and MTV had no impact on long-term outcomes in our cohort.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…This is in line with the results of a prospectively conducted study of Deantonio et al including 55 patients. They observed a statistically significant correlation between SUV max and T-stage of patients and no association with treatment response or survival of patients [12]. Similarly, baseline PET uptake parameters such as SUV max and SUV mean and MTV had no impact on long-term outcomes in our cohort.…”
Section: Discussionmentioning
confidence: 47%
“…Also for anal cancer, the role of PET-CT especially for disease staging and its impact on target volume definition has been studied before [10][11]. Several studies investigated the association of pretherapeutic PET-CT parameters with the oncological outcome of patients with anal cancer, with partly conflicting results [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…SUV max/peak/mean were non-significant predictors, which underlines the uncertain predictive value of SUV max for anal cancers. 15,20,38,39 TLG has previously been associated with treatment outcome for other cancer types, 40,41 and was found to be GTV, gross tumor volume; HPV, human papilloma virus; MTV, metabolic tumor volume; SUV, standardized uptake value; TLG, total lesion glycolysis. The abscissa signifies the p-value and hazard ratio of a parameter (column) when paired with a variable on the ordinate (row).…”
Section: Discussionmentioning
confidence: 97%
“…Positron emission tomography with fluorodeoxyglucose (FDG-PET) is recommended for the initial staging of anal SCC with detection of inguinal and pelvic lymph node involvement [19][20][21][22][23][24][25][26][27]. In recent years, several teams have investigated the prognostic value of semiquantitative PET data during pretherapy, post-therapy and the metabolic response phases of this pathology [20,[28][29][30][31][32][33][34]. While these studies showed a prognostic value for the MTV (metabolic tumour volume) using pretherapeutic FDG-PET, the methods for tumour mass segmentation are heterogeneous, with different fixed thresholds because of easier routine clinical use and the absence of a standardized method.…”
Section: Introductionmentioning
confidence: 99%